2018
DOI: 10.1007/s11920-018-0961-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Vulnerability to Prenatal Stress: a Review of the Recent Literature

Abstract: Most articles (k = 35) found evidence of either sex-specific associations (significant in one sex but not the other) or significant PNMSstress interactions for at least one child health outcome. Evidence for sex-dependent effects was strongest in the group of studies evaluating child neural/nervous system development and temperament as outcomes. There is sufficient evidence of sex-dependent associations to recommend that researchers always consider the potential role of child sex in PNMS programming studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 78 publications
6
84
0
1
Order By: Relevance
“…SA-born males (particularly WT males) exhibited reduced PPI, whereas SA-born female WT mice exhibited an anxiogenic profile in the EPM. These findings are consistent with other reports of sex-specific changes as a result of perinatal stress exposure, and how these differences might contribute to subsequent health outcomes of offspring 79 . One study showed greater prenatal maternal stressor sensitivity in male offspring for subsequent development of SZ spectrum disorders 80 .…”
Section: Discussionsupporting
confidence: 92%
“…SA-born males (particularly WT males) exhibited reduced PPI, whereas SA-born female WT mice exhibited an anxiogenic profile in the EPM. These findings are consistent with other reports of sex-specific changes as a result of perinatal stress exposure, and how these differences might contribute to subsequent health outcomes of offspring 79 . One study showed greater prenatal maternal stressor sensitivity in male offspring for subsequent development of SZ spectrum disorders 80 .…”
Section: Discussionsupporting
confidence: 92%
“…The potential for child sex to determine these associations also requires additional investigation. That our exploratory analyses provide some evidence that the association between prenatal mood entropy and 2-year child cognitive development scores appears to be present among girls, but not boys is consistent with findings from previous studies documenting sex differences in fetal programming (Sandman et al, 2013;Sutherland & Brunwasser, 2018). However, we did not find a sex difference in the association between maternal mood entropy and 6to 9-year child expressive language scores.…”
Section: Discussionsupporting
confidence: 91%
“…Adaptation of the maternal hypothalamic-pituitary-adrenal (HPA) axis is a key mechanism by which maternal stress modulates offspring neurodevelopment (3), and there is evidence that this mechanism operates in a sexually dimorphic manner (4). For, example, higher waking maternal salivary cortisol in pregnancy is associated with increased internalizing behaviours in female infants and reduced internalizing behaviours in males (5,6).…”
Section: Introductionmentioning
confidence: 99%